Multivariate Rayleigh, Rice, and Nakagami distributions and their applications in communication theory - Yu. A. Brychkov; N. V. Savischenko (Учёные записки Казанского университета: Серия Физико-математические науки)
A method was developed to calculate the symbol and bit error probabilities for coherent diversity reception of multi-position signal structures in a communication channel with additive white Gaussian noise (AWGN) and general fading described by the multivariate Rayleigh and Nakagami distributions, as well as the bivariate Rice distribution.